Synthesis of Short‐Chain Alkenyl Ethers from Primary and Bio‐sourced Alcohols via the Nickel‐Catalyzed Hydroalkoxylation Reaction of Butadiene and Derivatives. Issue 1 (9th December 2015) - Mifleur, Alexis; Ledru, Hélène; Lopes, Adrien; Suisse, Isabelle; Mortreux, André; Sauthier, Mathieu
Abstract: Hydroalkoxylation of butadiene has been performed in the presence of nickel precatalysts associated with chelating diphosphine ligands. High butadiene conversions and selectivities forming alkyl butenyl ethers were obtained with low catalyst loading. Reactions were performed with a wide scope of primary alcohols including benzylic alcohol derivatives and bio‐sourced alcohols. In the same way, the scope of dienes that can be reacted according to this reaction has been also studied. Substituted butadiene derivatives have shown a lower reactivity compared to butadiene. Isoprene formed OC5 alkenyl ethers with a high regioselectivity for one branched isomeric form. Abstract :